Evaluating Logistics Capabilities on Firm Performance of the Photonics Industry in Taiwan - Chi-Chang Lin; Po-Lin Lai (International Journal of Supply Chain Management, 2017)
This study empirically examined the impact of logistics capabilities on firm performance in the photonics industry. Structural equating modelling (SEM) was employed to test the research hypotheses with the use of data collected from a survey of 221 photonics manufacturing firms in Taiwan. Three dimensions were identified based on a factor analysis, including warehousing capability, information technology capability, and transportation capability. The research findings indicated that logistics capabilities positively influence firm performance. Information technology capability was found to be the most important logistics capability in the photonics industry, followed by warehousing capability, and transportation capability. There is also a discussion of the theoretical and managerial implications for the photonics industry.